1-Benzyl-3-methylimidazolium Tetrafluoroborate as an Efficient and Green Reaction Medium for the Synthesis of Pyrimido[1, 2-a]benzimidazoles. (April 2013) - Li, Yu-Ling; Cai, Gan; Liu, Xiao-Jun; Wang, Kai; Du, Bai-Xiang
A series of pyrimido[1, 2- a ]benzimidazole derivatives has been synthesised in high yields in the ionic liquid [bmim] + BF4 - . The structures of the products were characterised by IR, 1 H NMR, and HRMS spectroscopy. The reaction work-up is simple and the ionic liquid is easily separated from the products for reuse.